EBOLA AND COVID-19 EPIDEMICS: A DISCOURSE ON NIGERIA’S FOREIGN POLICY RESPONSES - BARILEDUM KIA; CALISTUS N DUMLE (International Studies Journal)
Diseases or epidemics does not respect international boundaries. Given this obvious fact, sovereign states are thus impelled to seek collective ways of addressing them and foreign policy is the crucial element in this endeavour. Nigeria, among other nation-states experienced Ebola and Covid-19 pandemics. How Nigeria responded to these epidemics was the focus of the study. The study employed historical and descriptive research method and obtained data from secondary source particularly website of world Health Organization, Nigeria’s Ministry of Health and other scholarly journals. This paper adopts complex interdependence and prospect theories as the framework of analysis. From the analysis the study revealed foreign policy measures adopted. These include setting up of screening and monitoring Centre at the nation’s Airports, facilitated the setting up of a regional solidarity fund, in which countries made contributions, initiated actions that adjudged Ebola epidemic as not only national and regional but also international emergency, donated huge sum to worst affected states like Guinea, Sierra Leone and Liberia. For COVID -19, In the case of Covid-19, Nigeria collaborated with major powers.  More than sixty inter agency members from the US mission worked with Nigerian counterpart to address the epidemic challenges in Nigeria. Its attracted $125 million, and more than 4 million doses of covid vaccine, 200 ventilators, personal protective equipment, and collaborated with the US to provide rapid response team. And training of over 200,000 military and civilian personnel on covid-19 control measures and technology transfer for virtual training. Based on the findings, the study recommends among others proper articulation and projection of health issues in the nation’s foreign policy and strengthening interface of health and foreign policy with the support of world health organization to assist in time of global health crisis.